2007
DOI: 10.1590/s0004-28032007000400009
|View full text |Cite
|
Sign up to set email alerts
|

Comparação entre exames de imagem e achados operatórios em doadores para transplante hepático intervivos

Abstract: RESUMO -Racional -No transplante hepático intervivos a anatomia da tríade portal e da drenagem venosa hepática do doador são de suma importância para o sucesso do procedimento. Objetivo -Analisar comparativamente os achados de exames de imagem no pré-operatório com os achados cirúrgicos em relação à anatomia da tríade portal e veias de drenagem hepática em doadores para transplante hepático intervivos. INTRODUÇÃOVariações anatômicas da tríade portal e da drenagem venosa hepática são freqüentes e de suma impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
3
1
Order By: Relevance
“…Our study provides an insight into the anatomical patterns found in Brazil. In view of our findings, it is possible to conclude that, because of the extensive miscegenation in Brazil, the indices of anatomical variation, despite sharing points of similarity, also present patterns of variations that differ considerably from those reported in the international literature, especially when we compare the patterns of celiac trunk variation with those found in homogeneous populations 2 , 9 , 14 , 32 .…”
Section: Discussioncontrasting
confidence: 41%
See 3 more Smart Citations
“…Our study provides an insight into the anatomical patterns found in Brazil. In view of our findings, it is possible to conclude that, because of the extensive miscegenation in Brazil, the indices of anatomical variation, despite sharing points of similarity, also present patterns of variations that differ considerably from those reported in the international literature, especially when we compare the patterns of celiac trunk variation with those found in homogeneous populations 2 , 9 , 14 , 32 .…”
Section: Discussioncontrasting
confidence: 41%
“…It is noteworthy that some isolated studies conducted in Brazil have analyzed the anatomical pattern of the hepatic artery and its branches in cadavers and during liver transplantations. However, studies dealing with the anatomical variations of the celiac trunk are really quite rare in Brazil, this being the aspect of our study that distinguishes it from others in the literature 2 , 9 , 14 , 22 , 30 .…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations